2023
DOI: 10.3847/psj/ace433
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric and Topographic Correlations within the Mare Ingenii Swirl Region: Evidence for a Highly Mobile Lunar Regolith

Deborah Domingue,
John Weirich,
Frank Chuang
et al.

Abstract: The spectrophotometric properties of two study areas in the Ingenii swirl region show that the combined effects of multiple processes are required to explain the regolith’s mineralogical and physical properties. Production of the swirl regions requires mobilization of the regolith in addition to preferential radiation shielding of subareas. The discovery of topographic correlations between on- and off-swirl (dark lanes) clearly shows that the on-swirl regions are statistically lower than the off-swirl dark lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 98 publications
2
5
0
Order By: Relevance
“…This interpretation agrees with Kinczyk et al (2022), who used LROC Narrow Angle Camera (NAC) imagery and the Hapke (2012a) model to find that differences in photometric behavior between on-and off-swirl regolith could be explained by the higher single-scattering albedo of the swirl material, without any variations in porosity or roughness. Domingue et al (2023), also using LROC-NAC imagery and the Hapke (2012a) model, likewise found no differences in microscale roughness between on-and off-swirl areas in the Mare Ingenii swirl region. While it remains possible that there are also textural differences between the on-and off-swirl surfaces, the data presented in Figure 22 suggest that the phase curves depend primarily on composition and optical maturity.…”
Section: Reiner Gamma Swirlmentioning
confidence: 76%
“…This interpretation agrees with Kinczyk et al (2022), who used LROC Narrow Angle Camera (NAC) imagery and the Hapke (2012a) model to find that differences in photometric behavior between on-and off-swirl regolith could be explained by the higher single-scattering albedo of the swirl material, without any variations in porosity or roughness. Domingue et al (2023), also using LROC-NAC imagery and the Hapke (2012a) model, likewise found no differences in microscale roughness between on-and off-swirl areas in the Mare Ingenii swirl region. While it remains possible that there are also textural differences between the on-and off-swirl surfaces, the data presented in Figure 22 suggest that the phase curves depend primarily on composition and optical maturity.…”
Section: Reiner Gamma Swirlmentioning
confidence: 76%
“…This is suggestive of more complex grain structures (such as agglutinates and more weathered grains) on-swirl, assuming similar composition and grain sizes across all units. However, as has been demonstrated, the compositions are not similar and the topographic differences may contribute to size-sorting of dust grains between on-swirl and off-swirl (Domingue et al 2022(Domingue et al , 2023. The small comparative increase in backward scattering seen on-swirl could be attributed to coarser regolith grains dominated by surface scattering (due to either compositional or structural differences) than the regolith grains in the diffuse-or off-swirl units.…”
Section: Discussionmentioning
confidence: 90%
“…Correlations between the swirl unit and photometrically derived surface roughness have been observed in some studies (Pinet et al 2000;Kreslavsky & Shkuratov 2003;Kaydash et al 2009;Hess et al 2020Hess et al , 2023 but not in others (Domingue et al 2023;Hess et al 2023). Those that have observed correlations often times are based on empirical models (Pinet et al 2000;Kreslavsky & Shkuratov 2003;Kaydash et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations